How do selective attentional processes contribute to maintenance and recall in children’s working memory capacity? - Roome, Hannah E.; Towse, John N.; Jarrold, Christopher (Frontiers in Human Neuroscience, 2014)
The development of working memory capacity is considered from the perspective of the active maintenance of items in primary memory (PM) and a cue-dependent search component, secondary memory (SM). Using, free recall, plus a more novel serial interleaved items task, age-related increases in PM estimates were evident in both paradigms. In addition to this, age-related improvements in attentional selectivity were observed, indexed by the recall of target and non-target information respectively. To further characterize PM, presentation modality was varied in the serial interleaved items task (auditory, visual and dual presentation). Developmental differences were found in the effectiveness of presentation formats. Older children’s recall was enhanced by the combination of labeled visual items and enduring auditory information, whilst the same format was detrimental to younger children’s recall of target information. The present results show how estimates of PM and SM in children relate to the development of working memory capacity, but measurement of these constructs in children is not straightforward. Data also points to age related changes in selective attention, which in turn contributes to children’s ability to process and maintain information in working memory.